Some Properties of a Class of Harmonic Multivalent Functions Defined by an Integral Operator (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Some properties of a class of harmonic multivalent functions defined by an integral operator are introduced, like, coefficient estimates, distortion property, extreme points, inclusion results and  closure under an integral operator for this class are obtained.